Banks’ Credit Ratings Inflation - Chodnicka-Jaworska, Patrycja (Olsztyn Economic Journal, 2017)
The aim of the paper is to verify the significance of the credit ratings’ inflation phenomenon of banks’ notes. First, a literature review was prepared. The following hypotheses were then put: Banks’ credit rating inflation has been observed. There are differences between the impact of the financial factors on banks’ credit ratings between notes that are given by one or more credit rating agencies to the same entity. The analysis was prepared by using probit panel data models. Data has been collected from the Thomson Reuters database. Long term issuer credit ratings proposed by S&P, Fitch and Moody were used as a dependent variable. As independent factors the financial indicators and macroeconomic variables were measured. The comparison of notes given by credit rating agencies suggests that notes that are given by all CRAs are similar. The same results were received when the notes given by two agencies were compared. Differences are observed only in the case of ratings given by one institution. If a CRA is bigger, notes proposed by them are higher. A list of variables that are taken by a particular credit rating agency can be created regardless of whether the evaluation is one or more CRAs. The strength of impact of the described factors is differentiated.